Delirium Diagnosis, Complication Recognition, and Treatment Knowledge among Nurses in an Italian Local Hospital: A Cross-Sectional Study - Andrea Ceccarelli; Maddalena Ballarin; Marco Montalti; Paola Ceccarelli; Silvia Mazzini; Alice Minotti; Davide Gori; Marco Senni (MDPI AG, 2024)
Delirium, a multifactorial condition with an acute onset and diverse clinical manifestations, poses a significant challenge in the care of hospitalized individuals aged 65 years and older. This study aimed to evaluate the level of knowledge among nursing healthcare personnel regarding the diagnosis, recognition of complications, and treatment of delirium. A paper questionnaire consisting of 18 multiple-choice questions was distributed to nurses in twelve operational units located in four facilities within a local hospital in a specific geographical region under the jurisdiction of the Romagna Local Health Authority in Italy. Out of 194 respondents, the overall acceptance rate was 64.2%. The findings revealed an insufficient understanding of delirium among the nursing staff, with more than 40% of respondents answering incorrectly to five out of nine questions related to delirium knowledge, diagnosis, prevention, and treatment. Notably, gender emerged as a significant determinant, with female participants exhibiting a substantial odds ratio (OR) of 3.50 (p = 0.011 and CI95% = 1.34-9.16) compared to their male counterparts, indicating a higher likelihood of receiving delirium training among females. Furthermore, prolonged tenure within the same work context was associated with a reduced likelihood of receiving delirium training compared to those with less than two years of experience (OR = 0.21, p = 0.034, and CI95% = 0.05-0.89 for 6-10 years of tenure; OR = 0.22, p = 0.038, and CI95% = 0.05-0.92 for over 10 years of tenure). This study underscores the urgent need for enhanced delirium education and improved strategies among nurses to effectively manage patients with delirium. The results advocate regular educational sessions utilizing diverse formats to comprehensively address knowledge gaps among nursing staff. This study was not registered.